2022
DOI: 10.17509/ijal.v12i2.51088
|View full text |Cite
|
Sign up to set email alerts
|

Nominal groups in deaf and hearing students’ narratives: A functional perspective

Abstract: Understanding the language aspect of deaf students in reference to their hearing counterparts plays a salient role in providing language teaching and learning treatment for the former.  As the initial effort to contribute to the language pedagogy for individuals with deafness, this study reveals the patterns of nominal groups in the Indonesian narratives of four deaf senior high school students and four hearing students of the same level.  A qualitative text analysis was adopted as the research design to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…A recent study carried out by Juliarta (2021) on the prepositional phrases of a novel also has indicated that two of the most common patterns in the novel refer to Preposition + Thing and Preposition + Deictic + Thing. The finding reported by the functional analysis of Manar (2022) has also shown that both deaf and hearing students tended to employ Thing only or Thing + Deictic in the nominal groups of their stories. Although nominal groups are different from prepositional phrases, the latter contains the former.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…A recent study carried out by Juliarta (2021) on the prepositional phrases of a novel also has indicated that two of the most common patterns in the novel refer to Preposition + Thing and Preposition + Deictic + Thing. The finding reported by the functional analysis of Manar (2022) has also shown that both deaf and hearing students tended to employ Thing only or Thing + Deictic in the nominal groups of their stories. Although nominal groups are different from prepositional phrases, the latter contains the former.…”
Section: Discussionmentioning
confidence: 66%
“…Despite their 'special' nature in language, deaf students are often expected to meet the expectation of their environment especially to write in the 'same' way as their hearing peers (Nodoushan, 2008;Spencer et al, 2003). The fact is that their written language has been characterized by unique linguistic features (Andrade et al, 2010;Favero et al, 2007;Lintangsari et al, 2019;Manar, 2022;Strong & Prinz, 1997;Wolbers et al, 2014), as the result of their limited verbal-linguistic input acquired from the environment. The linguistic challenges faced by students with deafness, for example, are reflected in the forms of grammatical features they adopt for making meaning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations